Calmodulin as a Key Regulator of Exosomal Signal Peptides - Kenji Ono; Mikio Niwa; Hiromi Suzuki; Nahoko Bailey Kobayashi; Tetsuhiko Yoshida; Makoto Sawada (Cells, 2022)
Signal peptides (SPs) and their fragments play important roles as biomarkers and substances with physiological functions in extracellular fluid. We previously reported that SP fragments were released into extracellular fluid via exosomes and bound to calmodulin (CaM), an exosomal component, in a cell-free system. However, it currently remains unclear whether CaM intracellularly interacts with SP fragments or is involved in the trafficking of these fragments to exosomes. Therefore, the present study examined the binding of CaM to SP fragments in T-REx AspALP cells, transformed HEK293 cells expressing amyloid precursor protein (APP) SP flanking a reporter protein, and their exosomes. APP SP fragments were detected in exosomes from T-REx AspALP cells in the absence of W13, a CaM inhibitor, but were present in lower amounts in exosomes from W13-treated cells. Cargo proteins, such as Alix, CD63, and CD81, were increased in W13-treated T-REx AspALP cells but were decreased in their exosomes. Furthermore, CaM interacted with heat shock protein 70 and CD81 in T-REx AspALP cells and this increased in the presence of W13. APP SP fragments were detected in intracellular CaM complexes in the absence of W13, but not in its presence. These results indicate that CaM functions as a key regulator of the transport of SP fragments into exosomes and plays novel roles in the sorting of contents during exosomal biogenesis.